Effect of Mobile Online Games on Everyday English Vocabulary Acquisition in AL-ULUM High School Students - Zahara, Fanni; Syahrina, Widya; Ananda, Rizky (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2025)
English is an international language, which has been used by many countries as a second language. To be able to speak English, everyone needs a lot of vocabulary. Vocabulary can be acquired using online games. Online games are widely used by students. The aim of this research is to find out whether there is an influence of the use of online games on the acquisition of English vocabulary for AL-ULUM SMA students, who are members of the extracurricular the flag-raising troop (Pasukan Pengibar Bendera or Paskibra). Researchers chose this topic because researchers saw that many students played online games in a free time. This research uses Psycholinguistic theory by Levelt. And behaviorism theory of language acquisition according to Skinner. The method in this research is a survey method with a quantitative approach. Researchers used a questionnaire as a research instrument. And some of these questions use a Likert scale. The results of this research show that it is true that online games have an influence on the acquisition of English vocabulary for AL-ULUM High School students. This can be seen from the answer data given by respondents, which has been explained briefly by the researcher. And with that result, it can be proven that the hypothesis “The use of online games has influenced the acquisition of English vocabulary for AL-ULUM High School students" is correct and accepted.